Development of Graphene Reinforced Metal Matrix Composite by Spark Plasma Sintering - Gao, Fei; Choi, Yongbum; Dobashi, Yosuke; Matsugi, Kazuhiro (International Journal of Engineering and Technology, 2018)
In order to obtain the high performance materials with high thermal conductivity, highã€€electrical conductivity, low thermal expansion, good mechanical properties and low density, Graphene has higher thermal conductivity comparison with other ceramic particle. In this study, graphene dispersed aluminum (Al) composites was developed by spark plasma sintering. Volume fraction of graphene were 10, 20 and 30 vol.%. Fabrication conditions of graphene dispersed aluminum (Al) composites were temperature of 813K and applied pressure of 80 MPa. As composite properties are affected by the dispersibility and volume fraction of the graphene particles, the relationship among the dispersibility of dispersant and the thermal conductivity and mechanical properties was investigated.Â Â